Microstructural and mechanical characterization of U-bend economizer failures: Integrating experimental testing and CFD simulation - Edi Purnomo; Ardi Wiranata; Deendarlianto; Muhammad Akhsin Muflikhun (Journal of Materials Research and Technology)
This study provides detailed defect analysis and investigation of the U-bend section in an economizer within a chemical industry heat exchanger, focusing on the implications after 25 years of operation. The analysis integrates experimental techniques such as tensile and flexural testing, hardness measurement, metallography, SEM-EDS, and OES, with CFD simulations to identify root causes of failure. Results show a tensile strength of 392.1 MPa and flexural strength of 1325.2 MPa, with uniform hardness across the heat-affected zone (HAZ) and unaffected areas. The SEM-EDS analysis indicates oxidation-related corrosion (FeO, Fe2O3, Fe3O4) due to welding defects. Moreover, CFD simulations highlight increased velocity vectors and wall shear stress around defect sites, leading to erosion. The root causes of failure are identified as welding defects and corrosion, exacerbated by operational stresses. The study emphasizes the importance of high-quality welding practices, routine inspections, and effective maintenance strategies to prevent early failure and enhance heat exchanger reliability and performance.